(untitled) (Revista Contexto & Educação, 2026)
This study aims to examine potential differences in performance on an experimental task by comparing students from monolingual, unimodal bilingual, and bimodal bilingual educational settings in public and private schools in the cities of Parnaíba and Teresina, in the state of Piauí, Brazil, considering only institutions that self-identify as bilingual. Bilingual education presupposes the use of two languages as media of instruction, with integrated exposure to both languages throughout the learning process. The Five Digits Test (FDT) (Sedó, De Paula, & Diniz, 2015) was employed to assess the efficiency of visual cognitive processing in children enrolled in monolingual classes, partial unimodal bilingual programs, full unimodal bilingual programs, and bimodal bilingual programs, with the aim of comparing their performance on tasks requiring visual cognitive abilities. The sample comprised 40 children aged 6 to 8 years (1st and 2nd grades of elementary education), with 10 participants in each educational category. The findings reveal differences in performance between monolingual and bilingual students, particularly between those enrolled in partial and full unimodal bilingual programs, thereby underscoring the need for institutions that identify as bilingual to reassess the extent of linguistic exposure provided in their curricula.